Improving quality attributes of sweet dumplings by germination: Effect of glutinous rice flour microstructure and physicochemical properties. (December 2021) - Wang, Hongwei; Zhang, Jing; Wang, Rui; Liu, Xingli; Zhang, Yanyan; Sun, Jianwei; Su, Ling; Zhang, Hua
Abstract: Current sweet dumplings made by raw waxy rice flour have some unsatisfactory storage and cooking quality such as high cracking rate and too sticky for swallowing. Hence, in order to produce high-quality dumplings, impacts of germination on microstructures and physicochemical characteristics of glutinous rice flours were evaluated, and how these technological properties affected dumpling quality was illustrated. It can be observed that germination reduced the relative crystallinity (from 29.15% to 26.00%) and short-range ordered degree of rice flour, which led to the increasement of swelling power for rice flour, but dramatically decreasing the characteristic viscosity and rigidity of flour paste and gel. And transformations of flour technological properties lowered the water mobility, water loss and cracking rate of sweet dumplings. Moreover, decreases in hardness, gumminess and adhesiveness were found in cooked germinated dumplings, and PCA analysis displayed significant correlations among flour microstructures, physicochemical characteristics, and textural quality of sweet dumplings. This study is beneficial to develop high-quality sweet dumplings through designing the microstructures and functionalities of rice flour with germination.